Being digital - Negroponte, Nicholas
Also available on cassetteBeing Digital is both a guide to the present state of our rapidly-changing digital age and a map for the future--how our lives will be shaped and enhanced by computer-related technology. Negroponte--Wired Magazine columnist and founding director of the MIT Media Lab--describes how advancements in computer technology and telecommunications will transform workplaces, households, and educational institutions. He explains how this revolution will change the way we live, think, and interact with one another and with technology, and foresees the challenges that lie ahead in developing truly global systems for delivering multimedia and other forms of digitally based information. Negroponte characterizes the development of future information delivery systems as a battle between atoms, the components of books and other physical resources, and bits, the basic building blocks of information